East Coast fever, a neglected tropical disease with an outdated vaccine approach?. Issue 11 (November 2022) - Kolakowski, Jeannine; Connelley, Tim; Lukacik, Petra; Pfuhl, Mark; Werling, Dirk
Abstract : Since its discovery, bovine theileriosis has caused major socioeconomic losses in sub-Saharan Africa. Acaricide resistance of the intermediate host, paucity of therapeutics, and lack of sufficiently cross-protective vaccines increase the risk of parasite spread due to global warming. Here, we highlight three important areas that require investigation to develop next-generation vaccines.